Pengembangan LKPD IPA Terpadu Berbasis Keterampilan Proses Sains pada Materi Cahaya dan Alat Optik untuk Meningkatkan Keterampilan Proses Sains Peserta Didik SMP Kelas VIII - Yumni Amalina; Ramlawati Ramlawati; Muhammad Aqil Rusli (Universitas Negeri Makassar, 2022)
This research was Research and Development aiming to produce Student Worksheet based on valid, practical, and effective science-process skills. This research used 4D Thiagarajan model. From the research results, it is showed that testing on experts indicate that the average of LKPD device score is valid with validity content of 1. It means that the developed LKPD is feasible in conceptually. Next, the percentage of LKPD practicality assessment results by educators shows very positive criteria with percentage 98%, it means that the educators can use the LKPD to be applied in learning process, as well as the percentage of learners’ responses on the developed LKPD shows very positive criteria with percentage of 96%, it means that the learners respond positively on the developed LKPD. Furthermore, the percentage of LKPD effectiveness assessment results as measured by science process skills assessed from N-gain result is 81.82% classified into medium category. Based on the research results, it can be concluded that the integrated LKPD of natural science based on developed science process skills satisfies validity, practicality, and effectiveness criteria.